Who made early Christianity?: the Jewish lives of the Apostle Paul - Gager, John Goodrich (American lectures on the history of religions, 2015)
Was the Apostle to the Gentiles the father of Christian anti-Judaism? -- The Apostle Paul in Jewish eyes : heretic or hero? -- Let's meet downtown in the synagogue : four case studies -- Two stories of how early Christianity came to be -- Turning the world upside down : an ancient Jewish life of Jesus